PEMBERDAYAAN GENERASI MUDA MELALUI PENINGKATAN PENGETAHUAN KEPEMIMPINAN DAN MANAJEMEN BAGI SISWA MA NU 03 SUNAN KATON KALIWUNGU - Sidiq, Asah Wiari; Romadon, Ahmad Sahri; Rizkiana, Citra (STIE Pelita Nusantara, 2024)
Youth is a human resource asset that continues to be fostered and explored to become a superior resource according to the character of the Indonesian nation. Educated students who have an understanding of leadership and management should be able to continue and change the world level later. The purpose of the service activity is to provide an increase in leadership and management knowledge for students as the younger generation in shaping their character so that they can become superior resources and have Indonesian personality. The problem that arises is that students are a young generation that does not easily live under pressure, tends to get bored easily and is identical as a reclining generation that is accustomed to advanced technology such as gadgets in daily life so that they are less able to manage their own lives and their organizations. The method of implementing community service activities will be carried out in the form of providing learning to the management of the Student Council MA NU 03 Sunan Katon Kaliwungu in the form of lectures in class about leadership and management knowledge, discussions and questions and answers. In addition, as an evaluation of service activities before learning, students will be given a pre-test questionnaire and after learning and discussYouth is a human resource asset that continues to be fostered and explored to become a superior resource according to the character of the Indonesian nation. Educated students who have an understanding of leadership and management should be able to continue and change the world level later. The purpose of the service activity is to provide an increase in leadership and management knowledge for students as the younger generation in shaping their character so that they can become superior resources and have Indonesian personality. The problem that arises is that students are a young generation that does not easily live under pressure, tends to get bored easily and is identical as a reclining generation that is accustomed to advanced technology such as gadgets in daily life so that they are less able to manage their own lives and their organizations. The method of implementing community service activities will be carried out in the form of providing learning to the management of the Student Council MA NU 03 Sunan Katon Kaliwungu in the form of lectures in class about leadership and management knowledge, discussions and questions and answers. In addition, as an evaluation of service activities before learning, students will be given a pre-test questionnaire and after learning and discussion, they will be given a post-test questionnaire. The results of the implementation of Community Service based on pre-test and post test evaluations showed an increase in leadership and management knowledge for students by 56.42% to 83.75% post-test. Keywords: Knowledge, Leadership, Management ion, they will be given a post-test questionnaire. The results of the implementation of Community Service based on pre-test and post test evaluations showed an increase in leadership and management knowledge for students by 56.42% to 83.75% post-test. Keywords: Knowledge, Leadership, Management